Bees of the genus Sphecodes Latreille 1804 of Siberia, with a key to species (Hymenoptera: Apoidea: Halictidae) - Astafurova, Yulia V.; Proshchalykin, Maxim Yu. (Zootaxa, 2015)
Twenty-one species of the bee genus Sphecodes Latreille are recorded from Siberia. Sphecodes schwarzi Astafurova & Proshchalykin, sp. nov. is described from Tyva Republic and Mongolia (Dornod Aimag). Five species: Sphecodes alternatus Smith, 1853, S. reticulatus Thomson, 1870, S. rufiventris (Panzer, 1798), S. pinguiculus Pérez, 1903, and S. spinulosus Hagens, 1875 are newly recorded from the Asian part of Russia and seven species: S. ferruginatus Hagens, 1882, S. hyalinatus Hagens,1882, S. longulus Hagens, 1882, S. miniatus Hagens, 1882, S. nippon Meyer, 1922, S. puncticeps Thomson, 1870, and S. scabricollis Wesmael, 1835 are recorded for the first time from Siberia. Sphecodes angarensis Cockerell, 1937 is newly synonymized under S. gibbus (Linnaeus, 1758). Illustrated keys for males and females of all species from Siberia and neighbouring Mongolia are provided.